The Influence of Marketing Mix Variables on Purchasing Decisions and Its Impact on Post-Purchase Customer Satisfaction of Royal Garden Residence Bali Housing (Study at PT Properti Bali Benoa) - Sugiono, Edi; Andini Nurwulandari; Christiani Junita (Open Access Indonesia Journal of Social Sciences, 2021)
The research objective is to determine the effect of: marketing mix variables (product, price, location and promotion) on purchasing decision variables, marketing mix variables on customer satisfaction variables, purchasing decision variables on customer satisfaction variables at Royal Garden Residence Bali housing with purchase decisions as a mediating variable. This research was conducted in the city of Bali, with the object of research being the residential consumers of Royal Garden Residence Bali as the population in this study, with a sample size of 150 respondents and using random sampling techniques. The data collection method is in the form of an online questionnaire via google form and whatsaap due to the situation in Indonesia which is currently being hit by the Covid-19 pandemic. The results of this study indicate that respondents have a good perception of the variable marketing mix, purchase decisions and post-purchase satisfaction Royal Garden Residence Bali. This is because the average value for all research variables is greater than 4 on the Likert scale. The results showed that the marketing mix variable both simultaneously and partially had a positive and significant effect on housing purchase decisions and the marketing mix variable had a positive and significant effect both simultaneously and partially on consumer satisfaction after purchasing Royal Garden Residence Bali housing, and purchasing decisions had a positive and significant effect. significant on consumer satisfaction after purchasing the Royal Garden Residence Bali housing. Then the research also proves that there is an indirect influence of the marketing mix variable on consumer satisfaction after purchasing the Royal Garden Residence Bali housing through the purchase decision. Promotion is the most dominant variable in increasing consumer purchasing decisions for Royal Garden Residence Bali housing.